Comparison of haemodynamic effects of lateral and sitting positions during induction of spinal anaesthesia for elective caesarean section - Kharge, Nutan Dileeprao; Mali, Ashish; Gujjar, Pinakin (International Journal of Research in Medical Sciences, 2017)
Background: Spinal anaesthesia avoids the problems associated with general anaesthesia such as airway manipulation, polypharmacy, postoperative respiratory problems, and cognitive dysfunction. It can be given in lateral and sitting positions. The aim of the present study was to compare the effect of induction position for spinal anaesthesia in elective caesarean section on hemodynamic, sensory and motor block characteristics and patient satisfaction. Methods: 120 ASA physical status I and II patients undergoing elective caesarean section were randomized to receive spinal anaesthesia in the lateral position or the sitting position. Hyperbaric bupivacaine (0.5%) was injected into the spinal space while the patients were either in sitting or lateral position at L3-L4 level. Effects on hemodynamic parameters, sensory block and motor block characteristics and patient satisfaction were analysed. Results: Demographic characteristics did not seem to have any impact on the overall outcome of the study. Induction position for spinal anaesthesia does not affect the hemodynamic parameters and incidence of side effects when adequate preloading is done. There was no statistically significant difference in the sensory level and motor level achieved. However lateral position appears to be more comfortable than sitting position (P <0.001). Conclusions: Inducing position for spinal anaesthesia did not affect haemodynamic stability and block characteristics in both the groups except that patients feel more comfortable in lateral position.